IOT: Controlling Pest and Managing Plant in Farming Sector - Mohd Noh, Muhammad Ashraf Aiman (IRC, 2020)
Controlling pest in farming sector has been comes with different method and it is common task that are doing by farmer to prevent and avoid their farming from the pest destroying the plant. This task and behavior have long been surmised on how to control and prevent the existence of pest in farming sector that might damage the plant. Pest are a major threat toward the farming sector. They are responsible for two major types of plant damage. The first is direct plant injury caused by insects eating leaves and burrowing holes in stems, fruits and/or roots. The second is indirect damage, where insects do little or no harm themselves, but spread to a plant bacterial, viral or fungal infection. In this regard, pest is one of the main organisms, often cause major thread to the plant health from plant to plant as numbers multiply. Controlling pests in agriculture is an important task. Pest control and management is a way to use effective methods to prevent longterm pest risks. It is necessary to maintain data on pests and all these resources as it can then be used by the number of automated agricultural systems. Web services can use knowledge in terms of ontology and make it available online. It will help farmers, not only in the field of agriculture, to control the pests in farming sector.